(3MQH JMQjQ GdYQGbs - (3cGXe eMeO Ydj TcQs
(3ChdgG (B:s
(3JegjO (B: (3GdYQGb bHd GdJMQjQ ; aj gPG GdHMK Sha fPcQ HGNJUGQ TOjO MGdI GdYQGb bHd MQH GdJMQjQ djWdY GdbGQF GdcQje HYde hOQGjI Ydi (B...s
(3BNQgG (B:s
... (3hbO cJfefG gPG SQG hde fYdfg NhaG ef SdWI GdfXGe GdHYKj GdUOGej hbO CNHQfGc Hg Gdjhe (B.. (3hMjK cGf GdcJGH cGedG HGOQJ Edi JOhjf cdGe GdYdGeI GdOcfhQ YHGS cGTa GdZcWGAs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdSjGSI hGdGLJeGYs